Quality of Life and Traditional Outcome Results at 1 Year in Elderly Patients Having Critical Limb Ischemia and the Role of Conservative Treatment. (February 2020) - Steunenberg, Stijn L.; de Vries, Jolanda; Raats, Jelle W.; Verbogt, Nathalie; Lodder, Paul; van Eijck, Geert-Jan; Veen, Eelco J.; de Groot, Hans G.W.; Ho, Gwan H.; der Laan, Lijckle van
Introduction: Revascularization is the cornerstone of the treatment of critical limb ischemia (CLI), but the number of elderly frail patients increase. Revascularization is not always possible in these patients and conservative therapy seems to be an option. The goals of this study are to analyze the 1-year quality of life (QoL) results and mortality rates of elderly patients with CLI and to investigate if conservative treatment could be an acceptable treatment option. Methods: Patients with CLI ≥70 years old were included in a prospective observational cohort study in 2 hospitals in the Netherlands between 2012 and 2016 and were divided over 3 treatment modalities: endovascular therapy, surgical revascularization, and conservative treatment. The World Health Organization Quality of Life (WHOQoL-Bref) instrument, a generic QoL assessment tool that includes components of physical, psychological, social relationships and environment, was used to evaluate QoL at baseline, 6 months, and 1 year. Results: In total, 195 patients (56% male, 33% Rutherford 4, mean age of 80) were included. Physical QoL significantly increased after surgical (10.4 vs 14.9, P < .001), endovascular (10.9 vs 13.7, P < .001), and conservative therapy (11.6 vs 13.2, P = .01) at 1 year. One-year mortality was relatively low after surgery (10%) compared to endovascular (40%) and conservative therapy (37%). Conclusion: The results of this study could not be used to designate the superior treatment used in elderly patients with CLI. Conservative treatment could be an acceptable treatment option in selected patients with CLI unfit for revascularization. Treatment of choice in elderly patients with CLI is based on multiple factors and should be individualized in a shared decision-making process.